2014
DOI: 10.4103/0974-8490.122914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phyllanthus emblica extract on cold pressor induced cardiovascular changes in healthy human subjects

Abstract: Background:Acute and chronic stress is a risk factor for the development and progression of coronary artery disease. Increased arterial stiffness is an independent marker for cardiovascular disease. Cold pressor test (CPT) is known to be associated with substantial activation of the autonomic nervous system.Objective:The aim of this study was to evaluate the effect of Phyllanthus emblica extract on cold pressor stress test induced changes on cardiovascular parameters and aortic wave reflections in healthy huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…In a prospective clinical study done to evaluate the hypolipidemic effect of Phyllanthus emblica, hypertensive patients achieved lower blood pressure levels (Gopa, Bhatt, & Hemavathi, 2012). In another study, Phyllanthus emblica reduced systolic and diastolic blood pressures along with augmentation index (Fatima, Pingali, & Pilli, 2014). Our results did not corroborate prior findings.…”
Section: Discussioncontrasting
confidence: 97%
“…In a prospective clinical study done to evaluate the hypolipidemic effect of Phyllanthus emblica, hypertensive patients achieved lower blood pressure levels (Gopa, Bhatt, & Hemavathi, 2012). In another study, Phyllanthus emblica reduced systolic and diastolic blood pressures along with augmentation index (Fatima, Pingali, & Pilli, 2014). Our results did not corroborate prior findings.…”
Section: Discussioncontrasting
confidence: 97%
“… 7–10 CAPROS ® is a standardized aqueous extract of the edible fruit of Phyllanthus emblica (amla) containing about 60% of low-molecular-weight hydrolyzable tannins such as Emblicanin-A, Emblicanin-B, Punigluconin, and Pedunculagin. 11 Recently, studies on Indian population investigating the effect of CAPROS on endothelial cell dysfunction and platelet aggregation in subjects with type 2 diabetes reported a significant decrease in lipid and blood glucose levels, as well as inhibition of platelet aggregation. 11–13 The current study sought to determine the effect of oral supplementation of CAPROS on CVD risk factors, including hyperlipidemia, C reactive protein (CRP), and high- sensitivity C reactive protein (hs-CRP) levels, and platelet aggregation in overweight/Class-1 obese adult human subjects from the US population.…”
Section: Introductionmentioning
confidence: 99%
“…This initiative could encourage the improvement of adherence to pharmacological treatment, offering a product with great popular appeal and pharmacological effects complementary to conventional therapies. [25][26][27][28][29][30][31] In this study, it was shown for the first time that prolonged treatment with an ethanol extract obtained from T. majus is able to prevent the evolution of renovascular hypertension in 2K1C rats, showing a significant reno-and cardioprotective effect. According to previous data, the renin-angiotensin system (RAS) played a prominent role in the oxidative stress and renovascular hypertension.…”
Section: Discussionmentioning
confidence: 96%